Keseimbangan Peran Dalam Keluarga Pada Pasangan Yang Menikah Di Bawah Umur Di Kecamatan Simeulue Barat Kabupaten Simeulue - Yulni, Yulni Fasiha (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Underage marriage occurs because teenagers do not think carefully about marriage. Adjustment in marriage for teenagers who marry underage is very important. The balance of the role of couples in families who marry underage must be maintained because they will bear great responsibility in building a household. The purpose of this study was to determine the phenomenon of underage marriage in West Simeulue District, specifically in Sinar Bahagia Village, Batu Ragi and Babul Makmur, what are the roles of husband and wife in families who marry underage in West Simeulue District, Simeulue Regency and how the impact of underage marriage on families and the surrounding community. This study uses a qualitative descriptive approach method where researchers will dig up in-depth information about the phenomena that occur. The data collection methods used are interviews, observations and documentation. Data analysis used is data reduction, data presentation and drawing conclusions. The results of this study indicate that those who marry underage are not merely coercion but because of financial or economic problems and some are matched by their parents and some even marry with the cause of pregnancy outside of marriage. The role of couples who marry below this carries out their respective roles in managing the household. Young marriage is still not accepted by the local community even though it is forced based on reasonable reasons.